AB0447 Anti-Phospholipid Positivity in Healthy Subjects: Evaluation of Risk for Thrombotic Event after A 5 Years Follow-Up. (15th July 2016) - Ceccarelli, F.; Massaro, L.; Morello, F.; Perricone, C.; Palermo, A.; Spinelli, F.R.; Alessandri, C.; Chistolini, A.; Valesini, G.; Conti, F.
Abstract : Background: Antiphospholipid syndrome (APS) is defined by the presence of thrombosis and/or pregnancy morbidity in combination with the persistent positivity of antiphospholipid antibodies (aPL): lupus anticoagulant (LA), anticardiolipin (aCL) and anti b2glycoprotein I antibodies (anti-b2GPI). These autoantibodies could be detected in other pathological conditions, such as autoimmune diseases (i.e. Systemic Lupus Erythematosus - SLE -), infectious diseases or cancer. Moreover, aPL could be identified in asymptomatic subjects (aPL carriers). Concerning this group, several questions are still unsolved, such as the risk of developing thrombotic events and the need of a prophylactic treatment. To date, the aPL carriers who are considered at higher risk of thrombosis are those with LA positivity, with triple positivity (LA+aCL+anti-β2GPI) and those with persistently positive aCL at high/medium titer. Data from the literature reported a risk ranging from 0 to 3.8% after a mean follow-up period of 2.3–8.7 years. It should be considered that 70% of the evaluated aPL carriers showed a concomitant autoimmune disease, which represents a risk factor for thrombotic events. Objectives: In this prospective study, we evaluated a cohort of aPL positive healthy subjects, in order to define the risk of developing thrombotic events, in comparison with a group of primary APS (PAPS) patients. Methods: In this longitudinal study, we consecutively enrolled 29 aPL carriers (M/F 3/26; mean age±SD 45.0±10.9 years) and 21 PAPS (M/F 5/16; mean age±SD 41.8±12.1 years). According with the study protocol, all patients underwent clinical assessment (collection of anamnestic data and traditional risk factors for cardiovascular disease) and laboratory evaluation (aCL, anti-β2GPI, LA, antinuclear antibody – ANA –, C3 and C4 serum levels; thrombophilic screening). Data concerning the familial cardiovascular history were collected. All subjects were evaluated every 6 months. Results: The comparison between aPL carriers and PAPS patients demonstrated as LA was significantly more frequent in aPL carriers (P=0.0001) while a similar percentage of triple positive patients was identified. Seventeen (58.6%) aPL carriers were treated with low dose aspirin (LDA), 2 (6.9%) with hydroxychloroquine. After a mean follow-up of 67.0 months (range 12–228), we identified an absolute risk to develop a thrombotic event of 0.03 (95% CI 0.001–0.238) and a relative risk of 0.7 (95% CI 0.02–6.44). In particular, a 55 years old female, treated with LDA, developed a thrombotic event after 84 months of follow-up, consisting in a minor stroke. The patient, without other risk factors, tested positive for LA and aCL at high/medium titer. Conclusions: To the best of our knowledge, this is the first study specifically designed to evaluate only aPL positive healthy subjects. The longitudinal evaluation identified, after a mean follow-up higher than 5 years, an absolute risk for thrombotic events of 0.03, with a relative risk of 0.7. As suggested by the case described, the presence of multiple aPL positivity, with high/medium titer antibodies, requires particular attention. Disclosure of Interest: None declared